Bridging the Gap: Civil-Military Cooperation in Humanitarian Logistics and Emergency Supply Chain Management - Habibie, Indra; Ganbat, Munkhzul; Rahmat, Hayatul Khairul; Jargalsaikhan, Tungsuu (PT. Civil Military Center, 2026)
Humanitarian logistics and emergency supply chain management have become increasingly complex due to the growing frequency and scale of disasters. In this context, civil-military cooperation plays a critical role in ensuring the timely and effective delivery of aid. This study examines how collaboration between civilian and military actors contributes to the efficiency and resilience of humanitarian logistics systems. Using a qualitative research approach that integrates a systematic literature review with contextual analysis, the study develops a conceptual framework linking operational capacity, coordination mechanisms, and governance structures. The findings reveal that military involvement significantly enhances logistical capabilities, particularly in transportation, infrastructure access, and rapid deployment. However, challenges related to coordination, institutional differences, and governance frameworks may limit effectiveness. The study contributes to the literature by providing an integrative perspective on civil-military cooperation in humanitarian logistics and offers policy-relevant insights for improving emergency supply chain management in disaster-prone contexts.